IDIOPATHIC GIANT CELL MYOCARDITIS PRESENTING AS SUDDEN CARDIAC DEATH- A RARE CASE REPORT - Permi, Harish S. (Journal of Health and Allied Sciences NU, 2014)
Idiopathic giant cell myocarditis is a disease of relatively young, predominantly healthy adults which is usually known to cause death in more than half of the cases of sudden death due to heart failure and ventricular arrhythmia. The typical histological features are myocardial necrosis and a rich cellular infiltration of lymphocytes, macrophages, eosinophils, plasma cells and multinucleated giant cells. We report a rare case of idiopathic giant cell myocarditis in a 32 year old healthy male who died suddenly and stress the need to consider as one of the cause of unexplained death in young adults on autopsy.
Keywords: Sudden cardiac death; Idiopathic giant cell myocarditis